Management and Outcome of Periprocedural Cardiac Perforation and Tamponade with Radiofrequency Catheter Ablation of Cardiac Arrhythmias: A Single Medium-Volume Center Experience. Issue 10 (October 2016) - Mujović, Nebojša; Marinković, Milan; Marković, Nebojša; Kocijančić, Aleksandar; Kovačević, Vladan; Simić, Dragan; Ristić, Arsen; Stanković, Goran; Miličić, Biljana; Putnik, Svetozar; Vujisić-Tešić, Bosiljka; Potpara, Tatjana
Abstract Introduction Cardiac tamponade (CT) is a life-threatening complication of radiofrequency ablation (RFA). The course and outcome of CT in low-to-medium volume electrophysiology centers are underreported. Methods We analyzed the incidence, management and outcomes of CT in 1500 consecutive RFAs performed in our center during 2011–2016. Results Of 1500 RFAs performed in 1352 patients (age 55 years, interquartile range: 41–63), 569 were left-sided procedures (n  = 406 with transseptal access). Conventional RFA or irrigated RFA was performed in 40.9% and 59.1% of procedures, respectively. Ablation was performed mostly for atrioventricular nodal reentrant tachycardia (25.4%), atrial fibrillation (AF; 18.5%), atrial flutter (18.4%), accessory pathway (16.5%) or idiopathic ventricular arrhythmia (VA; 12.3%), and rarely for structural VA (2.1%). CT occurred in 12 procedures (0.8%): 10 AF ablations, 1 idiopathic VA and 1 typical atrial flutter ablation. Factors significantly associated with CT were older age, pre-procedural oral anticoagulation, left-sided procedures, transseptal access, AF ablation, irrigated RFA and longer fluoroscopy time (on univariate analysis), and AF ablation (on multivariable analysis). The perforation site was located in the left atrium (n  = 7), right atrium (n  = 3), or in the left ventricle or coronary sinus (n  = 1 each). Upon pericardiocentesis, two patients underwent urgent cardiac surgery because of continued bleeding. There was no fatal outcome. During the follow-up of 19 ± 14 months, eight patients were arrhythmia free. Conclusion Incidence of RFA-related CT in our medium-volume center was low and significantly associated with AF ablation. The outcome of CT was mostly favorable after pericardiocentesis, but readily accessible cardiothoracic surgery back-up should be mandatory in RFA centers.